Pencatatan Sederhana untuk Meningkatkan Efisiensi dan Efektifitas Pengelolaan Keuangan pada UMKM Jawara Bojongsari Depok - Indawati, Indawati; Anggraini, Anggun; Ruhiyat, Endang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving the local economy, yet many still struggle with effective financial management due to a lack of basic bookkeeping skills. This community service activity (PKM), titled